Aplikasi Permintaan Perangkat Komputer Berbasis Web: (Studi Kasus : Departemen Mitra Bisnis Dan Layanan Teknologi Informasi PT. Pupuk Sriwijaya Palembang) - Marlindawati; Sahfitri, Vivi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Computer devices are essential hardware that support work across all fields, especially in a company setting. Therefore, it is expected that the computer equipment request process can be carried out accurately, quickly, and practically. With the implementation of a web-based computer device request application in the Business Partner & IT Services Department of PT Pupuk Sriwidjaja Palembang, the process of requesting, recording, and managing computer device data can be made more efficient. The tools used include the Laravel framework, utilizing the PHP programming language and a MySQL database. The design of the application is carried out using UML (Unified Modeling Language), with the diagrams used being the use case diagram, activity diagram, and class diagram. Data collection methods involved interviews and observations. The result of this research is expected to facilitate the process of requesting computer devices